Horizon Teks Walisongo: Membangun Demokratisasi Keberagamaan Individu - Ubaidillah Achmad (JURNAL INDO-ISLAMIKA, 2011)
This paper deals with the way how Muslim society applies its religious (Islamic) doctrines. It discusses how social values and behaviors taught by Walisongo are preserved by the society as to bring them to their life’s goals can realize the development of the quality of the model of both individual and collective religiosity, and argues that this in turn will build a hormonius social life within civil society, free from ethnical and religious conflicts.